A Treaty Right to Education - Carr-Stewart, Sheila (Canadian Journal of Education/Revue canadienne de l’éducation, 2001)
In the 1870s, representatives of the Crown and First Nations negotiated Treaties 1 to 7. Each included provision for education. This study focuses on the intent and expectations of education as a treaty right by the original signatories and the current divergent understandings. Today First Nations demand the fulfilment of their treaty right to education while Canada, despite constitutional authority and recent court decisions on treaties, administers educational services within the boundaries of its own legislation: the Indian Act. Honouring treaty commitments offers hope for educational opportunities and equity within the context of First Nation governance, traditions, and cultural milieu. L’article porte sur les droits des Premières nations en matière d’éducation, tels qu’ils ont été reconnus par les traités 1 à 7 conclus dans les années 1870. Les Premières nations exigent les respect des dispositions des traités dans ce domaine. Mais en dépit des décisions récentes des tribunaux, le Canada administre les services d’éducation selon sa Loi sur les Indiens. Le respect des obligations nées d’un traité offre de l’espoir pour l’enseignement et l’équité dans le contexte de la gouvernance, des traditions et du milieu culturel des Premières nations.